2016
DOI: 10.1021/acs.inorgchem.6b02284
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Magnetic Properties of KRuO4

Abstract: The crystal structure of KRuO is refined at both 280 and 3.5 K from neutron powder data, and magnetic properties are reported for the first time. The scheelite structure, I4/a, is confirmed at both temperatures. Atomic positions of greater accuracy than the original 1954 X-ray study are reported. The rare Ru ion resides in a site of distorted tetrahedral symmetry with nominal electronic configuration 4d(e). Curie-Weiss parameters are near free ion values for the effective moment and θ = -77 K, indicating domin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 12 publications
7
16
0
Order By: Relevance
“…To obtain the magnetic contribution to the heat capacity of Mn 6 Ni 16 Si 7 one needs to subtract that of a suitable lattice match, normally a paramagnetic iso-structural compound. 38 A previous study of the magnetic properties of Ti 6 Ni 16 Si 7 showed a Pauli paramagnetic like behaviour, 25 which was also observed in our measurements of magnetic susceptibility of the compound under an applied magnetic field of 1000 Oe (SI-3).…”
Section: Magnetic Susceptibilitysupporting
confidence: 86%
“…To obtain the magnetic contribution to the heat capacity of Mn 6 Ni 16 Si 7 one needs to subtract that of a suitable lattice match, normally a paramagnetic iso-structural compound. 38 A previous study of the magnetic properties of Ti 6 Ni 16 Si 7 showed a Pauli paramagnetic like behaviour, 25 which was also observed in our measurements of magnetic susceptibility of the compound under an applied magnetic field of 1000 Oe (SI-3).…”
Section: Magnetic Susceptibilitysupporting
confidence: 86%
“…We found this new phase to be isostructural to KRuO 4 , as determined from Rietveld refinements (Figure d), hence called hereafter Td‐NaRuO 4 . It crystallizes in I 4 1 / a space group, with however smaller cell parameters ( a = 5.24501(3) Å, c = 12.11654(13) Å for NaRuO 4 compared to KRuO 4 ( a = 5.6105(5) Å, c = 12.959(1) Å) . Akin in KRuO 4 , Ru, and Na are in tetrahedral and sevenfold coordination, (Figure e; Table S9, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…We have reported the synthesis of two new phases, namely, Li 2 RuO 4 and Td-NaRuO 4 which is isostructural to KRuO [21,23] From the compilation of the aforementioned Li(Na)(K) x RuO 4 phase diagrams, a trend seems to emerge; the smaller is the alkali, i) the higher is the coordination of Ru and ii) the lower is the oxidation state of Ru.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are other candidate materials with the diamond structure that possess such odd-parity multipoles. For example, KRuO 4 , whose crystal structure is similar to AOsO 4 , shows a staggered magnetic order along the z direction 48,49 , which implies the emergence of magnetic quadrupoles. Spinels AB 2 O 4 are another candidates, as the A sites comprise the diamond structure.…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%